2017
DOI: 10.1101/108894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individual differences in responsivity to social rewards: Insights from two eye-tracking tasks

Abstract: Correspondence to : Bhismadev Chakrabarti; b.chakrabarti@reading.ac.uk; +44 (0) AbstractHumans generally prefer social over nonsocial stimuli from an early age. Reduced preference for social rewards has been observed in individuals with autism spectrum conditions (ASC). This preference has typically been noted in separate tasks that measure orienting toward and engaging with social stimuli. In this experiment, we used two eye-tracking tasks to index both of these aspects of social preference in in 77 typical … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…This study evaluated two putative task measures of social reward responsivity in typically developing children using a tablet PC. We found a preference for social over non-social stimuli in a preferential looking task, replicating results from similar studies using lab-based eyetrackers [14,15]. This preference for social stimuli was not seen in the instrumental choice (button) task.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study evaluated two putative task measures of social reward responsivity in typically developing children using a tablet PC. We found a preference for social over non-social stimuli in a preferential looking task, replicating results from similar studies using lab-based eyetrackers [14,15]. This preference for social stimuli was not seen in the instrumental choice (button) task.…”
Section: Discussionsupporting
confidence: 87%
“…In a typical preferential looking paradigm for social versus non-social rewards, two competing stimuli-one of each type-are simultaneously presented while participants' gaze is tracked [12,13]. These studies have demonstrated that neurotypical children and adults gaze longer at social than non-social stimuli [13][14][15][16]. Children as well as adults thus demonstrate a robust preference for social rewards, when measured using visual preference paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, impulsive individuals may be more impacted by immediate influences of peers, whereas others may be more impacted by long‐term considerations concerning, for example, their reputation in the larger peer group (Meldrum et al., ; Meldrum, Miller, & Flexon, ; Thomas & McGloin, ). Furthermore, regarding social preferences, scholars have noted that some individuals care considerably more about the opinions, responses, and perceptions of their friends than do others (Chakrabarti, Haffey, Canzano, Taylor, & McSorley, ; Cohen & Prinstein, ; Fairbairn et al., ; Perrine & Aloise‐Young, ; Van Schoor, Bot, & Engels, ). This, too, would likely moderate the influence that peers have on any behavior, including crime and delinquency, in that individuals who place less weight on social rewards should logically be less influenced by the desires of the peer group…”
Section: Integrative Perspectives On Peers and Decision‐makingmentioning
confidence: 99%
“…This strong motivation to engage socially directs our attention to social signals, guides us to participate in behaviours that help us to establish, maintain, and enhance our relationships with others, and allows us to enjoy social interactions and to find them rewarding (Chevallier, Kohls, Troiani, et al, 2012). Social stimuli, such as dynamic and static displays of human faces and bodies, are valued by participants (Dubey, Ropar, & Hamilton, 2015;Williams & Cross, 2018;Hayden, Parikh, Deaner, & Platt, 2007) and engage attention more than non-social stimuli (Williams, Cristino, & Cross, 2019;Chakrabarti, Haffey, Canzano, et al, 2017;Gray, Haffey, Mihaylova, & Chakrabarti, 2018). For example, typically developed participants assign a higher value to smiling faces with direct gaze (Dubey et al, 2015) and human bodies moving naturally (Williams & Cross, 2018;Williams, Cristino, & Cross, 2019), compared to less social stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals also make daily decisions to direct behaviour towards positive stimuli such as social rewards (Fellows, 2004). Social reward processing has long been investigated behaviourally (Dubey et al, 2015;Williams & Cross, 2018;Williams et al, 2019;Chakrabarti et al, 2017;Hahn et al, 2016), and recent studies have also investigated the underlying neural mechanisms of social rewards in order to gain a greater understanding of reward processing in the typical population, as well as in individuals with social difficulties that are the hallmark of an autism spectrum condition (ASC) diagnosis (Kohls, Perino, Taylor, et al, 2013;Kohls, Peltzer, Schulte-Rüther, et al, 2011;Spreckelmeyer, Krach, Kohls, et al, 2009;Rademacher, Krach, Kohls, et al, 2010). These studies report that positive social feedback provided via faces activates the same reward-related brain regions, such as the ventral (nucleus accumbens; NAcc) and dorsal striatum (caudate nucleus and putamen), the amygdala, and the orbitofrontal cortex (OFC), as non-social incentives, such as money (Spreckelmeyer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%